Calculating the Electronic Transport Properties of Different Carbon Nanotube Based Intramolecular Junctions - Rashid Nizam; S. Mahdi; A. Rizvi; Ameer Azam (Iranica Journal of Energy and Environment, 2010)
The electronic structure and the conductance of carbon nanotube based metal/semiconductor/metal intramolecular junctions are investigated numerically. The nature of electronic states at the interfaces and in the semiconductor section is analysed with the help of tight-binding method. The quantum conductance of the system is calculated in the logical regime and its variations with energy have been observed. These quantum conductances have been compared among the different carbon nanotubes and that have been correlated with the pentagon and heptagon that formed in the intramolecular junction.